Retaining human capital: a danger zone for METAL STAR - Kong, S. M.; Rajendran, M.; Chan, Josephine I. L.; Nezakati, Hossein *; Joshi, J. P. (Emerald, 2021)
Learning outcomes: This case is to familiarise students with the peculiarities of managing people by focussing on human capital development (HCD). Through the case, students are exposed to the critical recruitment and retention issues faced by METAL STAR Limited Company (METAL STAR), which have a detrimental impact on their business operations. Through the novel use of the transformer-transactor-performer (TTP) profiling tool, students are able to recognise the importance of matching the right candidate to the right job as a solution for recruitment and retention issues. At the end of the case analysis and discussion, students would have a clear idea of the TTP Profiling tool and how to identify core elements needed for an effective and holistic recruitment-retention-separation strategy for a company. The knowledge gained is most valuable for the students as it can be applied to other companies having similar HCD issues. Case overview/synopsis: Carina Yew is the General Manager of METAL STAR, a sheet metal fabrication company in Penang, Malaysia. After more than 28 years of operations, METAL STAR has been adopting the same human resources (HR) processes and has failed to keep up with the current HR trends. Yew has to decide the best way to lead her company in transforming the HCD strategy to enable smooth and profitable business growth. Complexity academic level: The case is relevant for undergraduate, postgraduate or even executive students taking courses pertaining to HCD or human resource management.